Immigration and the U.S. Labor Market - Brian Duncan; Stephen Trejo (Centre for Research & Analysis of Migration (CReAM), Department of Economics, University College London, 2009)
Over the last several decades, two of the most significant developments in the U.S. labor market have been: (1) rising inequality, and (2) growth in both the size and the diversity of immigration flows. Because a large share of new immigrants arrive with very low levels of schooling, English proficiency, and other skills that have become increasingly important determinants of success in the U.S. labor market, an obvious concern is that such immigrants are a poor fit for the restructured American economy. In this chapter, we evaluate this concern by discussing evidence for the United States on two relevant topics: the labor market integration of immigrants, and the impact of immigration on the wages and employment opportunities of native workers. In these dimensions, the overall labor market performance of U.S. immigrants seems quite favorable. U.S. immigrants have little trouble finding jobs, and this is particularly true of unskilled immigrants. Most U.S. immigrants experience substantial earnings growth as they adapt to the American labor market. For most immigrant groups, the U.S.-born second generation has achieved socioeconomic parity with mainstream society; for some Hispanic groups, however, this is not the case. On the whole, immigration to the United States has not had large adverse consequences for the labor market opportunities of native workers. Therefore, with regard to the economic integration and labor market impacts of immigration, it is not obvious that the seemingly haphazard nature of U.S. immigration policy has led to unfavorable outcomes.
Keywords: 330